(untitled) - Newhall, Beaumont (London, 1982)
Since its first publication in 1937, this lucid and scholarly chronicle of the history of photography has been hailed as the classic work on the subject. No other book and no other author have managed to relate the aesthetic evolution of the art of photography to its technical innovations with such an absorbing combination of clarity, scholarship and enthusiasm
Keywords: Photography,Máy chụp ảnh; History,Lịch sử